LEGAL RECONSTRUCTION ON TAX INVOICES NOT BASED ON ACTUAL TRANSACTIONS: THE LEGAL MEANING OF THE ULTIMUM REMEDIUM PRINCIPLE IN SUSTAINABILITY OF TAXPAYER'S BUSINESS IN INDONESIA - Yuli T. Hidayat; Henry DP Sinaga (Scientia Integritas Utama, 2022)
The rampant cases of tax invoices transactions not based on actual transactions and handling that are not aligned and ignoring the principle of ultimum remedium, are crucial problems for the sustainability of the taxpayer's business that the tax authorities must immediately address. However, there have been several efforts in forming and enforcing laws in the field of taxation in terms of handling tax invoices not based on actual transactions; normative philosophical and juridical studies are needed by using the ultimum remedium principle and sustainable development buildings in answering the existing problem formulations. The findings of this study indicate that tax laws and regulations in dealing with tax invoices not based on actual transactions still ignore the ultimum remedium principle. There needs to be an ideal tax (legal) reconstruction in handling tax invoices not based on actual transactions in Indonesia through the meaning of the ultimum remedium principle and the business continuity of taxpayers. The ideal legal concept should become a policy structure, the provisions of which are contained in a Government Regulation and/or Minister of Finance Regulation.